2004
DOI: 10.1097/01.jom.0000121128.73921.a1
|View full text |Cite
|
Sign up to set email alerts
|

A Nested Case-Control Study of Prostate Cancer and Atrazine Exposure

Abstract: Elevated prostate cancer incidence was found at a plant producing atrazine that had an intensive prostate screening program. This study tested the relationship among atrazine exposure, prostate cancer, and the screening program. Twelve cases and 130 control subjects were selected from the original cohort. Prostate screening and occupational histories were abstracted from company records and atrazine exposures were estimated. Hire date was comparable for cases and control subjects. Nearly half of the control su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
22
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 8 publications
1
22
0
Order By: Relevance
“…Organophosphate insecticides used primarily in farming affect acetylcholine control in nerve stimulation, such as Phorate (sometimes in combination with family history, (Mahajan et al, 2006b) Fonfos (Mahajan et al, 2006a;Koutros et al, 2010b;Barry et al, 2011;, Coumaphos (Christensen et al, 2010) and fumigants, such as triazine herbicides (Mills and Yang, 2003), all were reported to contribute to a small increased risk of prostate cancer. Atrazine was also investigated by Hessel et al (2004) but no association was reported with prostate cancer. This was supported recently by Sathiakumar et al (2011), who indicated that there was no scientific basis for inferring the existence of a causal relationship between triazine exposure and the occurrence of cancer in humans.…”
Section: Budnik Et Al (2012) Germanymentioning
confidence: 99%
“…Organophosphate insecticides used primarily in farming affect acetylcholine control in nerve stimulation, such as Phorate (sometimes in combination with family history, (Mahajan et al, 2006b) Fonfos (Mahajan et al, 2006a;Koutros et al, 2010b;Barry et al, 2011;, Coumaphos (Christensen et al, 2010) and fumigants, such as triazine herbicides (Mills and Yang, 2003), all were reported to contribute to a small increased risk of prostate cancer. Atrazine was also investigated by Hessel et al (2004) but no association was reported with prostate cancer. This was supported recently by Sathiakumar et al (2011), who indicated that there was no scientific basis for inferring the existence of a causal relationship between triazine exposure and the occurrence of cancer in humans.…”
Section: Budnik Et Al (2012) Germanymentioning
confidence: 99%
“…In the United States, ATR is applied on crops such as corn, sugarcane, pineapples, macadamia nuts, and sorghum, as well as on highway and railroad rights-of-way and on evergreen trees (Environmental Protection Agency, 2003). Several epidemiological studies have investigated the link between ATR exposure and adverse human health outcomes (Hoppin et al, 2002;MacLennan et al, 2002;De Roos et al, 2003;Hessel et al, 2004). However, the human data at present are equivocal.…”
mentioning
confidence: 99%
“…Several epidemiological studies have investigated the link between ATR exposure and adverse human health outcomes (Hoppin et al, 2002;MacLennan et al, 2002;De Roos et al, 2003;Hessel et al, 2004). However, the human data at present are equivocal.…”
mentioning
confidence: 99%
“…Pesticides in general, and herbicides in particular, have been implicated as suspect causes in some studies (Fleming et al 1999;Willems 2003, 2004) and not in others (Aronson et al 1996;Zeegers et al 2004;Boers et al 2005). In one investigation of an herbicide production facility, detection bias due to enhanced PSA screening was found to be the most plausible explanation for an increased occurrence of prostate cancer (MacLennan et al 2002;Hessel et al 2004).…”
Section: Discussionmentioning
confidence: 93%